The Practice of Buying and Selling Used Clothing Imports on Perspective of Islamic Law and Positive Law: A Case Study of the Bang Jack Haurgeulis Store - Cholisa Fitri; Irvan Iswandi (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
During the development of the times, buying and selling is not merely undertaken between regions, but can also be undertaken between countries. This has become a separate business area for some middle to lower classes of society who want to open a business but with a capital that is not too large, namely by building stores with various types of imported used clothes. This study aims to find out how the practice between sellers and buyers of imported used clothing at Bang Jack store. This store is located on Jalan Raya Sumurwedi-Sumbermulya, Haurgeulis Sub District. The practice will be reviewed from the perspective of Islamic law using descriptive qualitative methods. Dealing with the results of research and discussion conducted by the researcher, it can be concluded that the practice of buying and selling at Bang Jack Haurgeuli’s store is based on the pillars and conditions that were in accordance with Islamic law. Then, based on the positive law, the sale and purchase of imported used clothing have violated state regulations as regulated in the Regulation of the Minister of Trade Number 51/M-DAG/PER/7/2015 and Law Number 7 of 2014 due to it is detrimental to customs duties on the state.